Need-based extension services towards community development for Sitio Aldea in Zambales, Philippines - Paraggua, Victoria Q.; Mobo, Froilan D.; Acuavera, Ronalyn C.; Villavicencio, Leah R.; Pasa, Geraldine C.; Guiang, Sheena Lee A. (Journal of Education and Learning (EduLearn), 2026)
The study aimed to identify the extension services in terms of community needs specifically economic, health, socio-cultural, and environmental needs of Sitio Aldea, Barangay Natividad in San Narciso, Zambales. The findings were used as basis in formulating a community extension program towards community development. The needs assessment, conducted by Philippine Merchant Marine Academy (PMMA), through its Department of Research, Development and Extension (DRDE), is important in identifying extension services that can effectively meet the priority needs of selected barangays in Zambales, which in this case, 3 barangays are selected dividing the research into three phases, and this is phase 1. This descriptive study used a survey questionnaire which consists of parts identifying the demographic profiles, economic, health, socio-cultural, and environmental-related needs of the community. The data gathered from 559 respondents revealed that Sitio Aldea is ‘highly in need’ of environmental, health and socio-cultural aspects and it is only in ‘need’ of economic aspects. Given these, an implementable community extension program and activities has been proposed. Its implementation is recommended, as well as an in-depth study on specific findings such as unemployment, education, and source of income. Finally, the replication of the study, to be conducted in another barangay for phase 2, is advocated.